EcoSol-agroecology networks respond to the Covid-19 crisis: building an economy of proximity in Brazil’s Baixada Santista region - Levidow, Les; Sansolo, Davis [UNESP]; Schiavinatto, Monica [UNESP] (Taylor & Francis, 2022)
In 2020–2021 the Covid-19 crisis worsened the harms from the hegemonic agribusiness model, while also providing opportunities for alternatives. Since long before the crisis, Latin American civil society networks had been building an agroecology-based solidarity economy (here EcoSol-agroecology for short). These networks have linked agroecological production methods with collective marketing through short food-supply chains (circuitos curtos), establishing closer relationships with consumers. Such initiatives have been expanded, despite adverse government policies and Covid-19 obstacles. This expansion has been widely understood as strengthening social proximities. As the analytical contribution here, EcoSol-agroecology networks build an ‘economy of proximity’, based on proximate purposes such as mutual aid, democratic self-management, women's leadership, food security and biodiverse resource conservation. These solidaristic purposes help to activate other proximities (geographical, organisational, institutional, and cultural), while also linking them. Collective capacities have developed those proximities in context-specific ways. This strategic perspective has informed EcoSol-agroecology networks in Brazil's Baixada Santista region, the site of grassroots voices in this case study. Diverse contributions have been integrated into a composite culture as a symbolic site of belonging. As global elites seek to restore the hegemonic agri-food system after the Covid-19 pandemic, a different future depends on building the social proximities of EcoSol-agroecology.
Keywords: Covid-19 crisis; EcoSol-agroecology; food and nutritional security; Hegemonic agribusiness model; short supply chains (circuitos curtos); solidarity economy (economia solidária)